Refusing to know a woman's place: the causes and consequences of rejecting stereotypes of women politicians in the Americas†. (2nd January 2017) - Smith, Amy Erica; Warming, Katherine; Hennings, Valerie M.
ABSTRACT: What are the sources and effects of gendered leadership stereotypes for women's representation? We explore the role of stereotypes in shaping public attitudes toward women's representation using AmericasBarometer survey data from 25 countries. We report three key results. First, the modal respondent in almost every country rejects gendered leadership stereotypes, affirming that women and men leaders are equally qualified on corruption and the economy. This holds even after we attempt to account for social desirability bias. Second, there are significant individual- and country-level determinants of stereotyping. In countries with higher women's representation and labor force participation but without gender quotas, citizens are more likely to choose pro-female and neutral responses over pro-male stereotypes. At the individual level, those rejecting stereotypes are less authoritarian, more supportive of labor market equality, and more leftist than those reporting pro-female stereotypes. Third, the consequences for representation vary by partisanship and country context. Pro-female leadership stereotypes boost support for women presidential candidates and for legislative gender quotas, but they matter less among copartisans of women candidates, and they matter more when women candidates are viable but gendered outsiders. Those rejecting leadership stereotypes altogether are less supportive of quotas.